Implementasi Metode Prototype Pada Perancangan Sistem Informasi Pengajuan Prakerin - Alam Supriyatna; Ahmad Fauzi (Universitas Binaniaga Indonesia, 2023)
Arridho Islamic Vocational School was established in 2007 consisting of 4 (Four) Competency Expertise/Departments: (1) Akuntansi Keuangan dan Lembaga; (2) Bisnis Daring dan Pemasaran; (3) Teknik Komputer dan Jaringan; dan (4) Teknik Bisnis Sepeda Motor. From the expertise/department competencies, Arridho Islamic Vocational School has an allocation of 17 classes, a total allocation of around 36 students per class. Industrial relations are very risky in data collection and very detailed job demands, so that students can carry out their internship well. Not a few students submitted several internship applications before obtaining willingness from objects that had previously been submitted, especially if several objects provided willingness to these students. The media for the announcement of objects and information about internships were also not conveyed properly, because the media was full, damaged and covered with other information. This study has a formulation of the problem, namely how to submit independent submissions for students who have not been determined by the school where the internship will take place. Each submission must obtain a willingness from the industry/agency that will be used as a place for internships. If approved, a letter of application will be made and submitted to the company. This study aims to make the processing time in managing internship submissions better with data collection stored in the system to make it easier for the vice principal. The test results for the Submission Information System for Arridho Islamic Vocational High School were included in the very feasible category with a percentage value of 88.9% Processing Results of Expert Trial Questionnaire Data and 92% Processing Results of User Trial Questionnaire Data.